2007
DOI: 10.1126/science.1145336
|View full text |Cite
|
Sign up to set email alerts
|

Current-Induced Magnetization Switching with a Spin-Polarized Scanning Tunneling Microscope

Abstract: Switching the magnetization of a magnetic bit by injection of a spin-polarized current offers the possibility for the development of innovative high-density data storage technologies. We show how individual superparamagnetic iron nanoislands with typical sizes of 100 atoms can be addressed and locally switched using a magnetic scanning probe tip, thus demonstrating current-induced magnetization reversal across a vacuum barrier combined with the ultimate resolution of spin-polarized scanning tunneling microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
104
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 23 publications
0
104
0
Order By: Relevance
“…A number of experiments on current induced switching have been carried out previously [23][24][25][26][27] . From them it was found that the noise reduces the typical switching time, as one might expect.…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments on current induced switching have been carried out previously [23][24][25][26][27] . From them it was found that the noise reduces the typical switching time, as one might expect.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the pulse profile reaching the tunnel junction is applied to optimize the experiment's time response by actively shaping the incident pulses. Scanning probe microscope studies focus increasingly on measuring fast time-dependent processes at atomic dimensions, such as spin [1][2][3][4] and charge 5,6 dynamics or molecular motion. [7][8][9][10] Heterodyne frequency mixing 11 and pump-probe excitation schemes 2,[12][13][14][15] have been put forward as techniques to measure repetitive variations of the tunnel current in a scanning tunneling microscope (STM).…”
mentioning
confidence: 99%
“…The general theory was applied by Néel [2] and subsequently by Brown [21] to small ferromagnetic single-domain grains/nanoparticles. During the last decades these theoretical findings were endorsed by experiments performed at low temperatures in the presence of static magnetic fields [17], ac-magnetic fields [22,23] or spin-polarized currents [24,25]. In the present study we focus on the composite multiferroic structure, depicted in Fig.…”
Section: Introductionmentioning
confidence: 99%